Occupational Medicine, Respiratory Diseases, Occupational And Environmental Toxicology, University of Perugia: main activities - dell'Omo, Marco; Folletti, Ilenia; Gambelunghe, Angela; Murgia, Nicola; Paolocci, Giulia; Muzi, Giacomo (La Medicina del Lavoro, 2018)
The Division of Occupational Medicine, Respiratory Diseases and Occupational and Environmental Toxicology at the University of Perugia has been active since 1972 with the aim of working in the field of biomedical research, prevention, diagnosis and treatment of occupational and environmental diseases, as well as the training of students and specialists in Occupational Medicine. The Division is located at the University Department of Medicine, and Perugia (Unit of Occupational Medicine) and Terni General Hospitals. In 2017, the Unit of Occupational Medicine was identified as the “INAIL National Reference Structure - Occupational Diseases of the Respiratory System”. Numerous specialty care activities (in the hospital ward, outpatient and laboratory settings) are carried out at the Unit; among them, the specific inhalation challenges test, which constitutes the gold standard for the diagnosis of occupational bronchial asthma. The University staff also carries out teaching activities for students enrolled in the Degree Course in Medicine and Surgery and several Health Care Degree courses, and for Specialists in training at the University of Perugia. Research activities mainly concern: epidemiological and clinical studies on respiratory diseases induced by airborne pollutants and occupational allergens; indoor air quality and its health effects; toxicology of metals; toxic effects of powders and fibers on in vitro cellular systems; and, the epidemiology of tobacco smoking habit in working populations.